Características biopsicosociales que afectan la salud mental de los cuidadores principales de personas diagnosticadas con el trastorno de espectro autista (2024)
he objective of this research is to analyze the biopsychosocial factors that affect the family with a member diagnosed with autism spectrum disorder by identifying family dynamics, in this way the family becomes for the person with ASD (autism spectrum disorder) in the main support for overcoming behavioral, emotional and care problems.